2020
DOI: 10.3390/su12198154
|View full text |Cite
|
Sign up to set email alerts
|

The Land Sparing, Water Surface Use Efficiency, and Water Surface Transformation of Floating Photovoltaic Solar Energy Installations

Abstract: Floating photovoltaic solar energy installations (FPVs) represent a new type of water surface use, potentially sparing land needed for agriculture and conservation. However, standardized metrics for the land sparing and resource use efficiencies of FPVs are absent. These metrics are critical to understanding the environmental and ecological impacts that FPVs may potentially exhibit. Here, we compared techno-hydrological and spatial attributes of four FPVs spanning different climatic regimes. Next, we defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 90 publications
(117 reference statements)
0
24
0
Order By: Relevance
“…The results indicate that FPV systems have a higher PV panel packing density, which allows more PV capacity to be installed for a given surface area; however, because land-based PV systems are typically installed at optimal tilt angles, among other factors, they could have a slightly higher power generation efficiency (that is, they have a higher megawatt-hour per megawatt of PV capacity installed). Cagle et al [51] also recently published an empirical study that proposed three metrics to assess the land and water use efficiency of FPV systems at four installations in the United States: the land sparing ratio, water surface use efficiency, and water surface transformation. In many cases, despite the additional cost of the floatation system, the reduced cost of land acquisition and preparation results is a significant cost benefit to the FPV system, translating into as much as 26% lower development costs than ground-mounted PV [31,34,48,86].…”
Section: Land Use-related Co-benefitsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results indicate that FPV systems have a higher PV panel packing density, which allows more PV capacity to be installed for a given surface area; however, because land-based PV systems are typically installed at optimal tilt angles, among other factors, they could have a slightly higher power generation efficiency (that is, they have a higher megawatt-hour per megawatt of PV capacity installed). Cagle et al [51] also recently published an empirical study that proposed three metrics to assess the land and water use efficiency of FPV systems at four installations in the United States: the land sparing ratio, water surface use efficiency, and water surface transformation. In many cases, despite the additional cost of the floatation system, the reduced cost of land acquisition and preparation results is a significant cost benefit to the FPV system, translating into as much as 26% lower development costs than ground-mounted PV [31,34,48,86].…”
Section: Land Use-related Co-benefitsmentioning
confidence: 99%
“…Overall, stand-alone FPV systems have been shown to minimize the energy, water, and land trade-offs associated with energy project development. The first FPV installation at Far Niente Winery was installed on their wastewater pond to spare valuable wine-growing land, and a recent study showed that deployment of FPV can spare 2.7 times the amount of land than would be used for ground-mounted PV systems [51]. Hybrid systems can also effectively leverage existing hydropower infrastructure and reduce-if not eliminate-land-related impacts.…”
Section: Policy and Planning Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies addressing the potential impacts of FPV on ecosystem are, to-date, theoretical in their scope. 76 In order to understand the effects of the installed pilot FPV systems on the ecosystem, a large number of measurements were made under and in the vicinity The results of each cological measurement is discussed in the following five paragraphs.…”
Section: Ecological Impactsmentioning
confidence: 99%
“…Solar energy infrastructure spans terrestrial and aquatic settings (e.g., floatovoltaics; Armstrong et al, 2020;Cagle et al, 2020) that encompass various levels of human development. The integration of this infrastructure in the built and other humandominated environments can reduce or eliminate direct and indirect conflicts with biodiversity in alignment with SDGs 14 (Life Below Water) and 15 (Life on Land).…”
Section: Solar-wildlife Interactionsmentioning
confidence: 99%